Scalable Production of Eco-friendly Modified SiO2 as Demulsifier of Crude Oil - Soheila Javadian; Alireza Ramezani; S.Morteza Sadrpoor (Nanochemistry Research)
The extracted crude typically contains water-in-oil (w/o) emulsions. In this regrd, a novel demulsifier was synthesized in this research through modifying silica with benzalkonium chloride (SBKC). This demulsifier serves as a low-cost and biodegradable solution for the treatment of w/o emulsions. The amphipathic demulsifier was characterized by various techniques such as scanning electron microscope (SEM) and X-ray diffraction (XRD). In addition, the effects of temperature, standing time, and optimal demulsifier dosage were systematically investigated. Silica was modified with varying contents of BKC. According to the bottle test results, SBKC-20 achieved complete water separation from crude oil in 50 minutes (compared to 75 minutes for pristine silica). The studies showed the considerable effect of temperature on demulsification efficiency, as SBKC-20 separated water in just 1 minute at 95°C. Interfacial tension (IFT), optical microscopy, and contact angle measurements were also employed to better understand the demulsification mechanism. The ability of SBKC-20 particles to penetrate the oil-water interface was confirmed by IFT and optical microscopy. For example, SBKC-20 decreased the IFT between water and crude oil from 18.6 to 6.9 mN.m-1.